The Kinetochore: From Molecular Discoveries to Cancer Therapy - De Wulf, Peter; Earnshaw, William C.; SpringerLink (Online service) (New York, NY : Springer New York, 2009)
Kinetochores orchestrate the faithful transmission of chromosomes from one generation to the next. Kinetochores were first depicted over 100 years ago, but kinetochore research has progressed by leaps and bounds since the first description of their constituent DNA and proteins in the 1980s. "The Kinetochore: from Molecular Discoveries to Cancer Therapy" edited by Peter De Wulf and William C. Earnshaw presents a thorough up-to-date analysis of kinetochore and centromere composition, formation, regulation, and activity, both in mitosis and meiosis, in humans and "model" eukaryotic species, and at natural and mutant neocentromeres. Recently initiated translational research on kinetochores is also discussed as kinetochores are being mined as a very rich target for the next generations of anti-cancer drugs.
Centromeres and Kinetochores: An Historical Perspective -- The Basics of Chromosome Segregation -- The Centromere -- Neocentromeres -- Human Artificial Centromeres: Assembly of Functional Centromeres on Human Artificial Chromosomes -- Kinetochore Composition, Formation, and Organization -- Evolution of Centromeres and Kinetochores: A Two-Part Fugue -- Mitotic Spindle Assembly Mechanisms -- Kinetochore-Microtubule Interactions -- Post-Translational Modifications that Regulate Kinetochore Activity -- The Role of the Kinetochore in Spindle Checkpoint Signaling -- Kinetochore Regulation of Anaphase and Cytokinesis -- Roles of Centromeres and Kinetochores in Meiosis -- The Kinetochore-Cancer Connection -- The Kinetochore as Target for Cancer Drug Development.
Keywords: Medicine; Cancer research; Human genetics; Medical microbiology; Molecular biology; Virology; Cell biology; Biomedicine; Cancer Research; Cell Biology; Medical Microbiology; Molecular Medicine; Human Genetics; Virology; Electronic books